The social and economic importance of full employment - L. Randall Wray (Levy Economics Institute of Bard College, 2009)
Unemployment was singled out by John Maynard Keynes as one of the principle faults of capitalism; the other is excessive inequality. Obviously, there is some link between these two faults: because: since most people living in capitalist economies must work for wages as a major source of their incomes, inability to obtain a job means lower income. If jobs can be provided to the unemployed, inequality and poverty will be reduced although such policy will not directly address the problem of excessive income at the top of the distribution. Most importantly, Keynes wanted to put unemployed labor to work not digging holes, but in socially productive ways. This would help to ensure that the additional effective demand created by government spending would not be exhausted in higher prices as it ran up against bottlenecks or other supply constraints. Further, it would help maintain public support for the government's programs by providing useful output. And it would generate respect for, and feelings of self-worth in, the workers employed in these projects (no worker would want to spend her days digging holes that serve no useful purpose). President Roosevelt's New Deal jobs programs (such as the Works Progress Administration and the Civilian Conservation Corps) are good examples of such targeted job-creating programs. These provided income and employment for workers, actually helped increase the nation's productivity, and left us with public buildings, dams, trails, and even music that we still enjoy today. As our nation (and the world) collapses into deep recession, or even depression, it is worthwhile to examine Hyman P. Minsky's comprehensive approach to resolving the unemployment problem.
Keywords: J01; J21; J38; J48; J68; 330; Unemployment; employer of last resort; job guarantee; Keynesian policy; New Deal